A new low altitude species of Megophrys Kuhl and van Hasselt (Amphibia: Megophryidae), from Assam, Northeast India - Mahony, Stephen; Sengupta, Saibal; Kamei, Rachunliu G.; Biju, S. D. (Zootaxa, 2011)
Northeast Indian amphibian systematics and taxonomy is receiving increasing interest from herpetologists in recent years as remote, previously unexplored areas become more accessible for surveying. Even locations nearby cosmopolitan cities have the potential to produce taxonomic novelties. Herein we describe a new species of Megophrys from the foot-hills of the East Khasi Hills, northern Meghalaya, and adjacent forest in Garbhanga Reserve Forest, and Mayeng Hill Reserve Forest nearby the city of Guwahati, southern Assam. Megophrys megacephala sp. nov. is here compared with all Asian mainland congeners. This species altitudinal distribution is the lowest of all known Megophrys described from India and surrounding countries. A brief discussion is provided regarding some of the current difficulties faced by taxonomists working on the genus and several major problems in recent descriptions of congeners from Northeast India.